Efeito agudo do consumo de produto comercial com propriedades ergogênicas sobre o desempenho de mulheres durante testes físicos - Santini, Eliana (2013)
Introduction: The recurrent search for greatest results in sports and also in the esthetics issues has leading athletes and non-athletes to indiscriminate consumption of ergogenic drugs and supplements. Aims: To analyze the effect of utilization of products with ergogenic properties on the women’s performance during anaerobic physical tests. Methods: A double-blind experimental study, crossover, randomized and controlled, with administration of commercial thermogenic products with ergogenic property or placebo substance, was performed. Thermogenic products containing 2.31 mg.kg-1 of caffeine and 1,88 mg.kg-1 of Citrus aurantium, as well placebo products were administered to 8 women aged 18-30 (21,5±2,1), who were performing strength physical training at last for six months. After sample randomization, were made four trials and the groups were reversed (thermogenic group and placebo group). The static strength, as well muscle potency and resistance were evaluated by abdominal resistance tests, flexion and extension of the elbow, vertical jump, lumbar traction and handgrip strength, being the latter two variables assessed by mechanical dynamometer Results: There was no statistical difference in the performance of women during anaerobic tests (p>0,05) if compared the four trials, independent of the use thermogenic supplement (TS) or placebo product (PP). Conclusion: In the present study, the recommended dose of ergogenic products showed a non-significant effect during static strength, potency and muscle strenght. Moreover, we suggest that the inexperience of the subjects to perform the tests proposed, mainly vertical jump and arm flexion and extension, associated to unknown factors, caused no results in relation to performance improvement.